Armstrong : the adventurous journey of a mouse to the moon - Kuhlmann, Torben, 1982- (New York : NorthSouth, 2016)
A mouse decides to fly to the moon.
Translated from the German.
School Library Journal starred, August 2016
Booklist starred, August 2016
Pub Weekly, June 2016
Kirkus Starred, June 2016
Horn Book, April 2017
Keywords: Mice -- Juvenile fiction; Moon -- Exploration -- Juvenile fiction; Space flight -- Juvenile fiction; Mice -- Fiction; Moon -- Exploration -- Fiction; Space flight -- Fiction